2019
DOI: 10.1002/bab.1802
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, gene expression analysis, and in silico characterization of UDP‐N‐acetylglucosamine pyrophosphorylase from Bombyx mori

Abstract: The present study was aimed to explore the molecular and structural features of UDP‐N‐acetylglucosamine pyrophosphorylase of Bombyx mori (BmUAP), an essential enzyme for chitin synthesis in insects. The BmUAP cDNA sequence was cloned and expression profiles were monitored during the molting and feeding stages of silkworm larvae. The effect of 20‐hydroxyecdysone (20E) on BmUAP expression, and on silkworm molting was studied, which revealed that 20E regulates its expression. Multiple sequence alignment of variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 50 publications
(73 reference statements)
2
6
0
1
Order By: Relevance
“…Third, our data revealed that trachea had the highest HvUAP level, followed by foregut, midgut, hindgut and epidermis in H. vigintioctopunctata (Figure 1). Similar expression profiles of UAP have been observed in other insects 10 . In L. migratoria , for example, both LmUAP1 and LmUAP2 are widely expressed in the epidermis, foregut, midgut, hindgut, gastric caeca, Malpighian tubules, wing, trachea, fat body and muscle 28 .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Third, our data revealed that trachea had the highest HvUAP level, followed by foregut, midgut, hindgut and epidermis in H. vigintioctopunctata (Figure 1). Similar expression profiles of UAP have been observed in other insects 10 . In L. migratoria , for example, both LmUAP1 and LmUAP2 are widely expressed in the epidermis, foregut, midgut, hindgut, gastric caeca, Malpighian tubules, wing, trachea, fat body and muscle 28 .…”
Section: Discussionsupporting
confidence: 75%
“…Similar expression profiles of UAP have been observed in other insects. 10 In L. migratoria, for example, both LmUAP1 and LmUAP2 are widely expressed in the epidermis, foregut, midgut, hindgut, gastric caeca, Malpighian tubules, wing, trachea, fat body and muscle. 28 Correspondingly, TcUAP1 transcripts are widely distributed in larval midgut, hindgut, carcass (the entire body exclusive of gut), fat body and integument in T. castaneum.…”
Section: Hvuap Catalyzes the Biosynthesis Of Chitinmentioning
confidence: 99%
“…Furthermore, SfUAP expression significantly increased after each nymph molting, decreased during the inter-molting phase, and increased again before the next molt, which may be associated with nymph growth. This phenomenon was observed in L. migratoria and B. mori , in which UAP expression was periodically repeated at each molting cycle [ 25 , 34 ]. Additionally, we noted that the expression pattern of SfUAP was similar to that of chitin synthase, which is responsible for chitin formation in T. castaneum , Ostrinia furnacalis , N. lugens , B. mori , and S. furcifera [ 40 , 41 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…UAP (EC 2.7.7.23), a vital regulatory enzyme in the insect chitin biosynthesis pathway, specifically catalyzes the reaction of N -acetylglucosamine-1-phosphate with uridine triphosphate to yield UDP- N -acetylglucosamine (UDP-GlcNAc), which is an important substrate for the formation of chitin [ 24 , 26 ]. So far, UAPs have been isolated and characterized from several insect species, including Locusta migratoria [ 25 ], Bactrocera dorsalis [ 27 ], Tribolium castaneum [ 28 ], Spodoptera exigua [ 29 ], Aedes aegypti [ 30 ], Cnaphalocrocis medinalis [ 31 , 32 ], Leptinotarsa decemlineata [ 33 ], Bombyx mori [ 34 ], and Henosepilachna vigintioctopunctata [ 35 ]. Interestingly, most insects have been known to only possess a single UAP gene, except T. castaneum , L. migratoria , and L. decemlineata , all of which have two UAP genes ( UAP1 and UAP2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies on UAP were reported to illustrate its function in microorganisms, animals, and plants. UAP was reported in both prokaryotes and eukaryotes, while no homologous sequences were identified between them ( Palaka et al, 2019 ). In fungi, a singular UDP-GlcNAc pyrophosphorylase gene was reported in yeast ( Saccharomyces cerevisiae ), and loss-of-function mutant ( uap1 Δ) exhibited aberrant morphology including swelled or lysed ( Mio et al, 1998 ).…”
Section: Introductionmentioning
confidence: 99%